Sistem Pendukung Keputusan Pembelian Mobil Dengan Metode AHP Pada Bintang Motor Muara Bungo - Praptomo, Sidik; Jasmir, Jasmir (LPPM Universitas Dinamika Bangsa, 2023)
The high enthusiasm and interest of the public to own a private car provides a great opportunity for showroom business actors to improve service and sales. The absence of a system that can help provide recommendations to consumers makes it difficult for ordinary people to determine car purchases. In buying a car, consumers do not have a clear standard because there are so many aspects that are taken into consideration when making a purchase. This study aims to help consumers in choosing a car. With a decision support system, it is hoped that it can provide solutions to assist consumers in gett the appropriate car recommendations. The AHP method is a method whose main input is human perception so that the results of this method are close to desire, besides that the existence of a hierarchy allows solv complex or structured problems in sub-problems, and then compil them into a hierarchical form. A car purchase decision support system using the AHP method can help provide recommendations to consumers to make car buy decisions.